Development of OLP based automation program for cutting process improve of shape steel cutting robot - Kim Cheol Soon; Kim Myeong Hoon; Lee Soo Jun; Se-Han Lee; Jong-Keun Park (2008 International Conference on Control, Automation and Systems : 14-17 October 2008, 2008)
In this study, we developed a program module using Interactive Graphic Robotics Integrated Programming (IGRIP) and Microsoft Visual C++ in order to generate the tag points automatically. IGRIP can handle various types of robot models and can easily exchange graphic or numerical data with other CAD softwares. In a cutting process of shape-steels, however, IGRIP is inconvenient because users must manually generate all tag points. This program can read and analyze the macro data containing the information on cutting processes of shape-steels and can automatically generate digital models, named dasiaPartpsila and dasiaDevicepsila, tag points, and Graphic Simulation Language (GSL) program files useful in IGRIP.